2009
DOI: 10.1007/s00216-009-2885-7
|View full text |Cite
|
Sign up to set email alerts
|

Forensic analysis of dyed textile fibers

Abstract: Textile fibers are a key form of trace evidence, and the ability to reliably associate or discriminate them is crucial for forensic scientists worldwide. While microscopic and instrumental analysis can be used to determine the composition of the fiber itself, additional specificity is gained by examining fiber color. This is particularly important when the bulk composition of the fiber is relatively uninformative, as it is with cotton, wool, or other natural fibers. Such analyses pose several problems, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 45 publications
0
62
0
Order By: Relevance
“…However, an important factor in fiber examination is the passage of time. According to a study on fiber persistence, about 80% of transferred fibers are lost after the first 4 h. [1,6] It is, therefore, better for investigators to quickly collect garments and any other fibers for fiber analysis. Factors influencing how the fibers adhere to materials are the type of fiber transferred and the type of receiving material, as well as the extent of receiving material usage after transfer.…”
Section: Global Scenario Of Man-made Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an important factor in fiber examination is the passage of time. According to a study on fiber persistence, about 80% of transferred fibers are lost after the first 4 h. [1,6] It is, therefore, better for investigators to quickly collect garments and any other fibers for fiber analysis. Factors influencing how the fibers adhere to materials are the type of fiber transferred and the type of receiving material, as well as the extent of receiving material usage after transfer.…”
Section: Global Scenario Of Man-made Fibersmentioning
confidence: 99%
“…The transfer of trace material can link suspects, victims, and crime scenes by indicating contact of specific individuals with objects. [1,2] Many polymeric objects surround us in our daily lives, so there is a possibility that some of these polymers may be found at a crime scene. Fibers are one example, [2] as they can constitute some of the most important classes of forensic trace evidence, which often provide valuable information in a crime scene.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of trace evidence are, not limited to, examinations of glass, fiber, paint, debris, gunshot residue (GSR), building material, inks, toners, fingerprint residue and among others [13][14][15][16][17]. A variety of analytical techniques, including use of UVvisible microspectrophotometry [18], Fourier transform infrared spectroscopy (FTIR) with total attenuated reflectance (ATR) [19], Surface-enhanced Raman spectroscopy (SERS) [20], scanning electron microscopy with energy dispersed X-ray spectrometry (SEM-EDS) [21], inductively coupled plasma optical emission spectrometry (ICP-OES) [22], atomic absorption spectroscopy (AAS) [23], scanning electrochemical microscopy (SECM) [24], atomic force microscopy (AFM) [25], confocal laser scanning microscopy (CLSM) [26], gas chromatography with mass spectrometry (GCMS) [27] capillary electrophoresis [28] (CE) , and laser inducedbreakdown spectroscopy (LIBS) [29], have been used to provide fundamental knowledge and insightful information for forensic cases.…”
Section: Microbial Forensicsmentioning
confidence: 99%
“…High performance liquid chromatography is reasonable and sensitive for the signature analysis of BoNT; however, it requires a longer time for conducting on measurement than mass spectrometry. FTIR is fruitfully utilized for tap and fiber analysis [16,17]. Due to the fact that protein samples such as BoNT has significant overlap of IR signals in amide structure, FTIR might be limited and problematic in signature analysis of BoNT.…”
Section: Bont Signatures Analysismentioning
confidence: 99%
“…Although many colors can be distinguished visually, these assessments are subjective and may be affected by metamerism or the examiner's color vision [6,7]. More objective measurements can be obtained using instrumental methods such as microspectrophotometry (MSP), which is favored as a rapid and non-destructive method for characterizing the color of dyed fibers [8,9]. Several studies have demonstrated the capability of MSP to distinguish visually similar colored fibers based upon different chromophores in the molecular structure of their dyes [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%